(untitled) (International relations and international law Journal, 2016)
This article is about the problem of definition of energy security. Energy security has become one of the leading issues in the world today, however the concept of "energy security" has no standard definition. In this regard, the article considers opinions of various authors in this field, definitions of energy security given in the documents of some states and international organizations. Divergences in definition of energy security are connected with differences in the interests of the parties. One state is the exporter, and another – the importer, therefore, their interests are different. The supplier of oil is interested in the high prices of the production while the consumer wishes low prices. Even though it’s impossible now to find out the general definition, there are some similarities in the interests of the parties in this question. One thing is clear, energy security is one of the most important components of national security. And the parties have to reach a compromise to establish energy security in the world.